Indications and limitations of intensive renin-angiotensin-aldosterone system in chronic kidney disease - Wassermann, Alfredo Osvaldo; Migueles, Ricardo Alberto (Revista del Hospital Italiano de Buenos Aires, 2012)
Chronic kidney disease (CKD) prevalence is in continuous growth. High blood pressure and proteinuria are both markers of renal disease as well as therapeutic goals. Antihypertensive treatment with renin-angiotensin-aldosterone system (RAAS) inhibitors is strongly associated with nephroprotection, specially in proteinuric nephropathies. However, there is no agreement to consider proteinuria as a surrogate marker of CKD progression. RAAS remains active when angiotensin converting enzyme inhibitors or angiotensin receptor antagonist are indicated. Several investigations focused on strategies using drugs of these two pharmacological groups at supramaximal dose or associating them with each other, renin inhibitors, or aldosterone antagonists. All these intensive RAAS inhibition schemes were associated with greater proteinuria decrease compared to only one drug at antihypertensive dose, but effectiveness in end points remains unproven. Few studies with intensive RAAS inhibition have the time-length and sample size to reach evidence level. Those which had already finished failed to show endpoint benefits, and have shown increased cardiovascular and renal adverse events. Three studies which have the power to produce evidence are ongoing. In the meantime, intensive RAAS inhibition should be indicated by a trained specialist to a set of specifically selected patients
Keywords: renin; angiotensin; aldosterone; angiotensin converting enzyme inhibito; angiotensin receptor blocker; aliskiren; spironolactone; eplerenone; proteinuria; ESRD